Handling of Physical Evidence in Criminal Cases According to the Vietnamese Criminal Procedure Law - Chi, Nguyen Ngoc; Huong, Bui Thi Thu (VNU Journal of Science: Legal Studies, 2022)
Handling physical evidence is one of the criminal procedural activities, conducted by state bodies, during the process to resolve criminal cases. This activity requires the objectivity and fairness in the process of handling crimes, and the protection of legitimate rights and interests of relevant individuals and organizations; therefore, it contributes to the stability of the society and the development of the economy. Thus, a system of legal provisions on handling physical evidence have been developed to ensure the role of this activity, including not only criminal procedure law, but also provisions in the penal law, the civil law, and other relevant legal documents. Over the recent years, apart from successes, the implementation of activities to handle physical evidence in Vietnam in practice has revealed numerous limitations: the law on handling of physical evidence is not yet in line with the actual case settlement in practice; there are violations of the law on handling of physical evidence by competent persons, agencies, which might create conditions for abuse of powers, appropriating, damaging, losing physical evidence and might cause irreversible consequences. For those reasons, this article addresses theoretical and practical issues on the handling of physical evidence and, on that basis, proposes solutions to improve the efficiency  of this activity in criminal cases at the requests of the judicial reform in Vietnam. Keywords: Physical evidence, handling physical evidence, methods to handle physical evidence, criminal procedure.